Keretapi Tanah Melayu Berhad / Sharul Aiman Samsudin, Ahmad Dzulkifli and Muhammad Aizuddin Mohd Alias - Samsudin, Sharul Aiman; Dzulkifli, Ahmad; Mohd Alias, Muhammad Aizuddin (2017)
a. Background Of The Study This study focusing on the • effieciency of the system and the operation. • Connectivity of the rail line to improve the tourism sector b. Problem Statement Comman problem with KTMB are: i. Service Inefficiencies Timeliness factor The KTMB train has a problem with the delay of their train. This delay will cause: • Crowded station • Pasanger do not know the new train schedule • Pasanger cannot re-route their new journey